Porcine 2′, 5′-oligoadenylate synthetase 2 inhibits porcine reproductive and respiratory syndrome virus replication in vitro. (October 2017) - Zhao, Mengmeng; Wan, Bo; Li, Huawei; He, Jian; Chen, Xinxin; Wang, Linjian; Wang, Yinbiao; Xie, Sha; Qiao, Songlin; Zhang, Gaiping
Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) is acknowledged a fulminating infectious pathogen affecting the pig farming industry, and current vaccines and drugs could hardly inhibit this virus. The 2′, 5′-oligoadenylate synthetase (OASs) have antiviral activities, but the role(s) played by porcine OAS2 in protection against PRRSV infection are unknown. Here we found that endogenous expression of the porcine OAS2 gene could be promoted by interferon (IFN)-beta or PRRSV infection in porcine alveolar macrophages. Knockdown of porcine OAS2 led to increases in PRRSV replication, and OAS2 expression suppressed replication of PRRSV in a retinoic acid inducible gene I (RIG-I)-dependent manner, anti-PRRSV activity of porcine OAS2 would be lost if RNase L and OAS2 were both silenced. This discovery illustrates a pathway that porcine OAS2 responses to host anti-PRRSV function. Highlights: We firstly found that porcine 2′, 5′-oligoadenylate synthetase (OAS2) could inhibit the PRRSV replication. Porcine OAS2 suppressed replication of PRRSV in a RIG-I-dependent manner and enhanced RIG-I-mediated IFN induction.